Association of the CPT1A p.P479L Metabolic Gene Variant With Childhood Respiratory and Other Infectious Illness in Nunavut - Collins, Sorcha A.; Edmunds, Sharon; Akearok, Gwen Healey; Thompson, J. Robert; Erickson, Anders C.; Hildes-Ripstein, Elske; Miners, Amber; Somerville, Martin; Goldfarb, David M.; Rockman-Greenberg, Cheryl; Arbour, Laura (Frontiers in Pediatrics, 2021)
Objective: Infectious illness, including lower respiratory tract infection (LRTI), is a leading cause of childhood morbidity and infant mortality in Inuit children in Nunavut Canada. The carnitine palmitoyltransferase 1A (CPT1A) p.P479L variant is common in arctic Indigenous populations of Alaska, Canada and Greenland. CPT1A is a fatty acid oxidationn enzyme expressed in the liver, immunocytes and other tissues, and is needed to use fats for energy during fasting. Previous association of the variant with early childhood infectious illness and infant death has been challenged because of sample size and limited adjustment for confounders. We evaluated whether the p.P479L variant is associated with infectious illness in Inuit children of Nunavut, Canada. Methods: We conducted a retrospective reviewed clinical charts review of 2225 Inuit children (0-5yrs) for infectious illness (including otitis media, gastroenteritis and hospital admission for LRTI), prenatal, perinatal, and socioeconomic indicators, subsequently linking to CPT1A genotype. Multivariable logistic regression adjusted for birth characteristics, breastfeeding, maternal smoking, food insecurity and socioeconomic indicators. Results: Overall, 27% of children were hospitalized for LRTI, 86% had otitis media and 50% had gastroenteritis. The p.P479L allele frequency was 0.82. In multivariable analysis, p.P479L homozygosity was associated with LRTI admission (aOR:2.88 95%CI:1.46-5.64), otitis media (aOR:1.83, 95%CI:1.05-3.21) and gastroenteritis (aOR:1.74, 95%CI:1.09-2.77), compared to non-carriers. Conclusion: Children homozygous for the p.P479L variant were more likely to experience infectious illness than non-carriers, including hospitalization for respiratory tract infections. Given the role of CPT1A in immunocytes, our findings indicate that more study is needed to determine if there is a on the role of the variant in immune response is needed. Continued Inuit involvement is essential when considering next steps.